2009
DOI: 10.3846/1648-0627.2009.10.285-297
|View full text |Cite
|
Sign up to set email alerts
|

Mobingo kaip diskriminacijos darbuotojų santykiuose poveikis organizacijos klimatui

Abstract: Santrauka. Straipsnyje apžvelgiama organizacijos klimato tyrimų raida ir sandara, analizuojamas mobingo kaip diskriminacijos darbuotojų santykiuose poveikis organizacijos klimatui. Organizacijos klimato tyrinėjimo ištakos -psichologiniai tyrinėjimai, į klimato tyrimus išsivystę praėjusio amžiaus ketvirtojo dešimtmečio pabaigoje. Apžvelgiant organizacijos klimato tyrimų raidą ir charakteristikas galima teigti, kad nėra bendros organizacijos klimatą apibūdinančios charakteristikų sampratos, kitaip tariant, autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…M. Kristenson et al (2001) compared the impact of mobbing on cardiovascular diseases in Lithuania and Sweden, V. Malinauskien÷ et al (2005) related the effects of terrorization with cardiovascular diseases of teachers, P. Žukauskas and J. Vveinhardt (2009a) extended the concept of mobbing in the aspect of discrimination and found the following: socio-demographic characteristics of mobbing victims in the public and private sector organizations, the relationship of mobbing with the organizational climate, the expression of mobbing in accordance with the areas of professional field of activity, modelling managerial decisions on the prevention and intervention (Vveinhardt, 2009;Žukauskas, Vveinhardt, 2010Žukauskas, Vveinhardt, , 2011Vveinhardt, Žukauskas, 2012).…”
Section: Organizational Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Kristenson et al (2001) compared the impact of mobbing on cardiovascular diseases in Lithuania and Sweden, V. Malinauskien÷ et al (2005) related the effects of terrorization with cardiovascular diseases of teachers, P. Žukauskas and J. Vveinhardt (2009a) extended the concept of mobbing in the aspect of discrimination and found the following: socio-demographic characteristics of mobbing victims in the public and private sector organizations, the relationship of mobbing with the organizational climate, the expression of mobbing in accordance with the areas of professional field of activity, modelling managerial decisions on the prevention and intervention (Vveinhardt, 2009;Žukauskas, Vveinhardt, 2010Žukauskas, Vveinhardt, , 2011Vveinhardt, Žukauskas, 2012).…”
Section: Organizational Contextmentioning
confidence: 99%
“…The problem must be addressed by improving working conditions, reducing physical load, increasing awareness on the subject (Johns, Menzel, 1999). The research conducted in Lithuania has shown that the occurrence of mobbing in the activities of hotels and restaurants reaches almost 6 percent (Vveinhardt, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ir tik nedaugelis Lietuvos mokslininkų (Vasiljevienė 2004(Vasiljevienė , 2006Malinauskienė et al 2005;Barkauskaitė, Žadeikaitė 2006;Eičinas, Vilkevičius 2006;Sąlyga et al 2008;Žukauskas, Vveinhardt 2009aŽukauskas, Vveinhardt , 2009b. Mobingo samprata, reiškinio įtaka organizacijos klimatui pateikti žurnalo "Verslas: teorija ir praktika" 2009 m. 10(4) (Vveinhardt 2009) numeryje, pasiūlytas mobingo kaip diskriminacijos darbuotojų santykiuose gerinant Lietuvos organizacijų klimatą diagnozavimo modelis.…”
Section: įVadasunclassified
“…were discussed from the perspective of human resource evaluation especially broadly and consequently. From the perspective of organizational climate, the widest research was carried out on: the connection between organizational climate and employee interrelations (Vveinhardt, 2009); changes in the measurements of organizational climate when planning the performance improvement and seeking greater efficiency (Rekasiute-Balsiene, 2005); striving of the organization to be successful (Vveinhardt & Skindaraite, 2012), etc.…”
Section: Introductionmentioning
confidence: 99%